Eksistensi Bahasa Indonesia Melalui Media Sosial Untuk Generasi Milenial - Feby Annisa Yasmin; Risky Putri Jasmine (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Language is a condition for humans to think which makes humans get the process of understanding and knowledge. The data collection method used is the observation method with reading and note-taking techniques. The data analysis method used is the matching method with orthographic matching techniques and referential matching techniques. The results of the study show that currently, the Language and Books Development Agency (formerly the Language Development and Development Agency) of the Ministry of Education and Culture (Kemendikbud) of the Republic of Indonesia uses social media as a means of fostering Indonesian language in the digital era, Indonesian people, especially social media accessors can improve self-ability in the use of Indonesian, as well as increasing positive attitudes so that people have awareness, pride, and loyalty to Indonesian language norms in the digital era. Indonesian has not functioned properly and correctly. Most people who speak feel that they have a sense of inferiority in their behavior, so they feel more respected, and educated if in everyday speech events, both in the variety of speech and writing, they insert a pile of foreign terms, even though there are already equivalent words in Indonesian.